Sistem Informasi Penjualan Pada Toko Mebel Asri - Andriyani .; Yustina Retno wulandari (Universitas Sahid Surakarta, 2010)
Sales of Furniture at Asri Store done manually which services to consumers and recording of goods sold recorded modest. This allows for the difference in the numberof inventory items and the difficulty in knowing revenue each month. Therefore need to be made selling computer-based information systems as an alternative to avoid errors in processing the data on the old system. Sales information system that will be made is built and developed using data modeling with DFD, diimplementasian using visual basic programming language and the use of Microsoft Access databases in data management and storage. The information generated from the sale of informationsystems that report the best-selling items, income statement, and statement of sales transactions. Based on the results of testing with user subjective evaluation, a total of12 respondents (60%) assess quickly the system in service, 11 respondents (55%) assess the performance of the system makes it easy, 13 respondents (65%) believe the system is easy to use good, 13 respondents (65%) assess the system easy to understand